PENGARUH PERSEPSI MASYARAKAT TERHADAP MANAJEMEN PENGELOLA PADA PEMELIHARAAN TAMAN KAYU PUTIH KOTA PEKANBARU - Nurlaili Husna; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Green Open Space (RTH) is part of the open spaces of an urban area filled with plants, plants and vegetation (endemic, introduction) to support the direct and / or indirect benefits generated by the RTH within the city. Taman Kayu Putih is an active environmental park which is one of the most open type of Green Open Space (RTH) and can be directly benefited by park users especially in the community around Simpang Empat Village. Based on the observations that the authors do in the field, seen that the condition of Kayu Putih garden is very unkempt, unkempt, damaged, and dirty with piles of garbage. On the other hand, the demand for increased comfort for the community is increasingly needed so as to encourage the need to conduct a study on park management in order to give satisfaction to the community. Based on the above matter, it is deemed necessary to study the perception of the community, especially the Taman Kayu Putih visitors as one of the people's attitude in conveying their aspirations, because the people's perception towards social service facility is one of them is meaningful and the most important thing can be the stages Beginning for more participatory and sustainable urban park management policy. Based on the above, the researcher is interested to study how the influence of public perception on managers management on the maintenance of Taman Kayu Putih Pekanbaru.The concept of theory used is management according to G. R Terry, who said that there are 4 variables that need to be considered in management are: 1. Planning, 2. Organizing, 3. Implementation, 4. Supervision. This research uses quantitative method with descriptive data. In collecting the data the researchers used questionnaire and obsevation techniques with a samples taken as many as 95 people using a simple random method.The results showed that the perception of the community on the maintenance of the Kayu Putih garden states 74.7% strongly agree if involved in the management of Taman Kayu Putih Pekanbaru. On the management of maintenance management Taman Kayu Putih Pekanbaru is in the category quite well. And public perception have influence to management of management at maintenance of Taman Kayu Putih Pekanbaru.Key Words: Public Perception, Management, Taman Kayu Putih